Prevalence and Management of Primary Dysmenorrhea among Female High School Students in Yangon Adventist Seminary - Nan Deborah Thein; Nilawati Soputri (Sagamedia Indo Press, 2022)
Background: Primary dysmenorrhea is painful menstrual bleeding that occurs in the absence of any underlying pelvic disease. It is the most common gynecological problem among women, especially in teens. Objective: This study aims to determine the prevalence and management of primary dysmenorrhea among female high schools in Yangon Adventist Seminary. Method: A descriptive study was carried out among female high school students at Yangon Adventist Seminary. 69 students participated voluntarily in this study, which was selected using a purposive sampling method. The questionnaire was distributed through a google form, and data collection was from august 21 2022 to 23 August 2022. Results: The mean age of the participants was 16.19 years with a standard deviation + of 1.19 years. The prevalence of primary dysmenorrhea was 82.6%. The methods used by respondents to relieve menstrual pain were taking medication prescribed by the doctor 93%, self-medication 96.5%, applying heating pads or compress 98.2%, tea or herbs 96.5%, bed rest 98.2%, traditional medicine 5.3%, consuming hot fluids 7% and wine 3.5%. Conclusion: The prevalence of primary dysmenorrhea was high. Bed rest and applying heating pads or compresses were the most common methods used by the respondents to relieve menstrual pain.